Addressing linguistic and social sustainability: morphological awareness among multilingual students with varying first-language literacy levels - Rose, Judi; Mutta, Maarit; Maijala, Minna (Walter de Gruyter GmbH, 2026)
English reading comprehension skills are essential in Finland, as English has become the dominant foreign language learned in schools and it is widely used in Finnish society. Therefore, acquiring adept English skills is essential to ensure equal education and job opportunities. Generally speaking, children with a migrant background may face many challenges in reading comprehension (Grabe & Yamashita 2022; Kaukko et al. 2022), putting their linguistic and social sustainability at a disadvantage compared to children born to Finnish-speaking parents. They often have to navigate in several languages, depending on how long they have been in the Finnish education system. This study explores adolescents’ (ages 13–14, N=62) morphological awareness with varying first language literacy levels. As morphological awareness is considered a key contributor to reading comprehension, we assume that low morphological awareness will result in low English reading comprehension proficiency. To investigate this assumption, tests to measure morphological awareness and English reading comprehension were administered and the obtained data were analyzed quantitatively. The results of the study support our assumption. Although the results indicate immense variation in test scores, a positive correlation was found in the impact of morphological skills on English reading comprehension. The results of the study will be used to develop better ways to address morphological awareness in EFL classrooms and thereby contribute to increased social sustainability.